Principles of Justice in The Authority of the Land Bank as A State Institution in Land Management in Indonesia - Rindananto, David Aji; Rosmini, Rosmini; Arifudin, Nur (Universitas Syiah Kuala, 2025)
The orientation and substance of the Land Bank Agency, are more on investment and economic development that contain risks. The problematic Land Bank regulation in the Job Creation Law and the Land Bank PP has the potential to conflict with the objectives of agrarian reform and constitutionality in the agrarian sector. Management rights that function publicly and are determined as rights with a civil character contain risks, namely the potential to cause deviations in management rights and denial of the agrarian constitutional consensus. The initial goal for the welfare of the community, especially the weak economic group, can change to be in the interests of capital research targets through analysis of the relationship between norms, content analysis, combining theory-norms, and legal principles. The impact of the implementation of the Land Bank as the basis for the development of the Land Bank infrastructure, where if the land acquisition process actually reduces the welfare of the landowners of the land used by the Land Bank, this land acquisition process will certainly become a new problem.